2019
DOI: 10.3389/fphar.2019.00183
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of L-Arginine Induced Gastrointestinal Motility Disorder in Rats Using UPLC-MS After Magnolol Treatment

Abstract: Background and Purpose: Magnolol, as the main active ingredient of Traditional Chinese Medicine, can significantly improve gastrointestinal motility disorders (GMD). In the present study, metabolomics was used to investigate the mechanism of magnolol improving L-arginine induced GMD in rats. Experimental Approach: SD rats were randomly divided into control group, model group and magnolol treated group. L-arginine was injected intraperitoneally in model and magnolol groups to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Liver fibrosis is a chronic progressive liver disease with complex pathological mechanisms and there are no safe and effective treatment tools [1, 4]. The mean of combining metabolomics with network pharmacology to dig data extensively can effectively overcome these problems [24, 29]. Metabolomics analyzes and detects the levels of small molecules in body fluids to determine which compounds have significant abnormalities and to reveal the mechanisms of disease development [30].…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis is a chronic progressive liver disease with complex pathological mechanisms and there are no safe and effective treatment tools [1, 4]. The mean of combining metabolomics with network pharmacology to dig data extensively can effectively overcome these problems [24, 29]. Metabolomics analyzes and detects the levels of small molecules in body fluids to determine which compounds have significant abnormalities and to reveal the mechanisms of disease development [30].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of citrulline with Lactobacillus helveticus (a bacteria strain that can catabolize arginine/citrulline for cell growth) exhibited synergistic effects in promoting NO production and improving intestinal epithelial barrier functions [98]. In a study investigating the effects of magnolol (an active ingredient utilized in traditional Chinese medicine) in L-arginine-induced gastrointestinal motility disorder, it was reported that magnolol alleviated gut disorder via reducing NO production, and its relaxing properties on GIT [193]. Another study employing the combination of dasatinib and quercetin as senolytic drugs in aged mice revealed that their long-term treatment reduced senescence cells, reduced inflammatory markers, and altered metabolic signatures in the intestines, thus improving gut health [194].…”
Section: (D) In Vitro Effects Of Citrulline and Quercetin On Intestinal Cell Integritymentioning
confidence: 99%
“…In previous studies, Lee et al indicated that Magnolia officinalis extract had a wide range of inhibitory effect against H. pylori growth and reduced mucosal inflammation and epithelial damages in the stomach of the H. pylori -infected mice [ 34 ]. Our previous studies also found that magnolol reduced nitric oxide content and increased serotonin content, promoted gastrointestinal motility, and alleviated L-arginine-induced gastrointestinal motility disorder in rats [ 35 ]. Nitric oxide is involved in both gastrointestinal mucosal defense and injury [ 15 ].…”
Section: Discussionmentioning
confidence: 96%